PPARγ and RXR Ligands Disrupt the Inflammatory Cross‐talk in the Hypoxic Breast Cancer Stem Cells Niche. Issue 11 (November 2014) - Papi, Alessio; De Carolis, Sabrina; Bertoni, Sara; Storci, Gianluca; Sceberras, Virginia; Santini, Donatella; Ceccarelli, Claudio; Taffurelli, Mario; Orlandi, Marina; Bonafé, Massimiliano
Abstract Cancer stem cells (CSCs) are affected by the local micro‐environment, the niche, in which inflammatory stimuli and hypoxia act as steering factors. Here, two nuclear receptors (NRs) agonists, i.e. pioglitazone (PGZ), a ligand of peroxisome proliferator activated receptor‐γ, and 6‐OH‐11‐O‐hydroxyphenanthrene (IIF), a ligand of retinoid X receptors, were investigated for their capability to interference with the cross‐talk between breast CSCs and the niche compartment. We found that IIF potentiates the ability of PGZ to hamper the mammospheres‐forming capability of human breast tumours and MCF7 cancer cells, reducing the expression of CSCs regulatory genes (Notch3, Jagged1, SLUG, Interleukin‐6, Apolipoprotein E, Hypoxia inducible factor‐1α and Carbonic anhydrase IX). Notably, these effects are not observed in normal‐MS obtained from human breast tissue. Importantly, NRs agonists abolish the capability of hypoxic MCF7 derived exosomes to induce a pro‐inflammatory phenotype in mammary glands fibroblasts. Moreover, NRs agonist also directly acts on breast tumour associated fibroblasts to downregulate nuclear factor‐κB pathway and metalloproteinases (MMP2 and MMP9) expression and activity. In conclusion, NRs agonists disrupt the inflammatory cross‐talk of the hypoxic breast CSCs niche. J. Cell. Physiol. 229: 1595–1606, 2014. © 2014 Wiley Periodicals, Inc.